AHIMSA PARAMO DHARMAH- A JAIN PERSPECTIVE (International Journal of Food and Nutritional Sciences, 2022)
Non Violence is the peak of sustainable practices. The restrictive meaning of adding the word “non” implies negation of any concept. Ahimsa certainly has a broader meaning and strict understanding of not resorting to violence and thus promoting peace. Non Violence should be practiced in thought, words and action. Hence it is rightly said “Manasyekam, vachas ekam, karmanyekam Mahatmanam.” Of the high souls, mind, body and speech are one and the same. Controlling oneself does not mean not caring for others and giving free course to oneself but also showing empathy and compassion to all living beings. Therefore peace and non-violence is not passive response but a positive, optimistic and constructive behavior. The ritualised compassion and repentance of lapses is best described in Jain Philosophy. A famous shloka roughly translated as “Seeking pardon of all living beings and requesting for friendship, goodwill and free of enmity” speaks volumes of Jain Philosophy tending towards peace as a means of Social Welfare. The neutrality of matured human mind is best described as “A mind never agitates in adversity, never elates in prosperity, bereft of passion, fear and anger the intellect stays firm.” The paper makes an attempt to examine the primary tenets of Jain Philosophy to create awareness on global peace for harmonious existence. Sources and references will be drawn from prakrit texts highlighting the teachings of Jainism, translated editions, journal papers and related articles. An attempt would be made to promote “Loka hita and Loka Sukha” The principle aim is to reaffirm “Vasudhaiva Kutumbakam” Concept.